PENGARUH MOTIVASI, PERSEPSI DAN LAMA PENDIDIKAN TERHADAP MINAT MAHASISWA UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Yuneriya, Nanda Estie; Sarwono, Aris Eddy; Kristianto, Djoko - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT This study aims to determine whether there is a difference between the interest to follow PPAk student state and private universities. Variable used is the old educational motivation and perception. In this study the object used is UMS and UNISRI for PTS while for PTN is UNS. Of the 55 questionnaires distributed in this study all back in full. From the test results obtained by the Independent sample t test t value 0,914 < 1,96 with a probability of 0,365 results > 0,05 means that there is no difference in interest student to follow PPAk between state and private universities. Although known to the average student interest PTN to follow PPAk higher than student PTS, but it did not prove for real difference between the interest of students to follow PPAk, this is because the student has not entered the real world of work so as not understanding the true benefits of completing PPAk. Keywords: Accounting Professional Education, Motivation, Perception.